2005
DOI: 10.1086/432679
|View full text |Cite
|
Sign up to set email alerts
|

Hot and Diffuse Clouds near the Galactic Center Probed by Metastable \documentclass{aastex} \usepackage{amsbsy} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{bm} \usepackage{mathrsfs} \usepackage{pifont} \usepackage{stmaryrd} \usepackage{textcomp} \usepackage{portland,xspace} \usepackage{amsmath,amsxtra} \usepackage[OT2,OT1]{fontenc} \newcommand\cyr{ \renewcommand\rmdefault{wncyr} \renewcommand\sfdefault{wncyss} \renewcommand\encodingdefault{OT2} \normalfont \selectfont} \DeclareTextFontCommand{\t

Abstract: Using an absorption line from the metastable (J ; K) ¼ (3; 3) level of H þ 3 together with other lines of H þ 3 and CO observed along several sight lines, we have discovered a vast amount of high-temperature (T $ 250 K) and lowdensity (n $ 100 cm À3 ) gas with a large velocity dispersion in the central molecular zone (CMZ) of the Galaxy, i.e., within 200 pc of the center. Approximately three-fourths of the H þ 3 along the line of sight to the brightest source we observed, the Quintuplet object GCS 3-2, is infe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(166 citation statements)
references
References 89 publications
11
153
2
Order By: Relevance
“…The CMZ consists of non-axisymmetric clouds with complicated structure (Oka et al 2005;Kruijssen, Dale & Longmore 2015). Our simulation implies that such nonaxisymmetric clouds are a natural outcome of magnetic activity in the Galactic center.…”
Section: Non-axisymmetric Structurementioning
confidence: 80%
See 1 more Smart Citation
“…The CMZ consists of non-axisymmetric clouds with complicated structure (Oka et al 2005;Kruijssen, Dale & Longmore 2015). Our simulation implies that such nonaxisymmetric clouds are a natural outcome of magnetic activity in the Galactic center.…”
Section: Non-axisymmetric Structurementioning
confidence: 80%
“…Observations of the atomic and molecular interstellar medium in the inner Milky Way exhibit large noncircular motion of the gas (Rougoor & Oort 1960;Scoville 1972;Liszt & Burton 1978;Bally et al 1987;Oka et al 1998;Tsuboi, Handa & Ukita 1999;Sawada et al 2004;Oka et al 2005;Takeuchi et al 2010). Among various possible explanations for the noncircular motion, de Vaucouleurs (1964) raised a possibility that the gas responds to a stellar bar potential of the Milky Way.…”
Section: Introductionmentioning
confidence: 99%
“…The density of these CRs in the GC can be derived from measurements of the absorption line of the ionised molecular hydrogen (H + 3 ). Thus, Oka et al (2005) and Goto et al (2008Goto et al ( , 2011 found an unusually high ionization rate in the GC, which is not observed in other parts of the Galactic Disk. The ionization rate, ζ, is almost uniform throughout of the GC on scales about 200 pc, ζ ∼ (1 − 3) × 10 −15 s −1 .…”
Section: Introductionmentioning
confidence: 62%
“…Yusef-Zadeh et al (2013a) assumed that these electrons ionize diffuse hydrogen gas and generate also the 6.4 keV line. As follows from Oka et al (2005) the rate of ionization is almost constant throughout the GC region; this means an almost uniform distribution of the electrons there. Yusef-Zadeh et al (2013a) derived parameters of these electrons from the observed nonthermal radio flux from the GC region 2 • × 0.85 • .…”
Section: Ionization By Cr Electrons In the Intercloud Medium Stationmentioning
confidence: 92%
See 1 more Smart Citation